Model-based glycemic control in a malaysian intensive care unit: Performance and safety study - Abu-Samah A.; Knopp J.L.; Razak N.N.A.; Razak A.A.; Jamaludin U.K.; Suhaimi F.M.; Ralib A.M.; Nor M.B.M.; Chase J.G.; Pretty C.G. (Dove Medical Press Ltd, 2023)
Patient treatment; Stars; Blood glucose measurements; Control settings; Critically-ill patients; Glycemic control; Malaysians; Model based controls; Patient specific; Pilot trial; Intensive care units; glucose; Article; clinical assessment; cohort analysis; controlled study; disease severity; female; glucose blood level; glycemic control; health care planning; human; hypoglycemia; incidence; intensive care unit; intervention study; major clinical study; Malaysian; male; patient safety; pilot study; protocol compliance; stochastic model